1974
DOI: 10.1051/gse:19740103
|View full text |Cite
|
Sign up to set email alerts
|

EFFETS DES GÈNES s ET k SUR LA CROISSANCE ET L'EFFICACITÉ ALIMENTAIRE CHEZ LE POUSSIN DANS 2 CROISEMENTS ET AVEC 2 NIVEAUX PROTÉIQUES

Abstract: RÉSUMÉNous croisons des coqs hétérozygotes (sk, SK) à des poules de génotype (sk-)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…II). Concerning the latter, our results agree with those of Lowe and Merkley [10] and Guillaume [7] although the latter results concerned chicks aged between 0 and 20 days. Our results also agree with those of Dunnington et al [3].…”
Section: Food Intakesupporting
confidence: 92%
See 1 more Smart Citation
“…II). Concerning the latter, our results agree with those of Lowe and Merkley [10] and Guillaume [7] although the latter results concerned chicks aged between 0 and 20 days. Our results also agree with those of Dunnington et al [3].…”
Section: Food Intakesupporting
confidence: 92%
“…According to some authors, especially Guillaume [7], a favourable effect associated with the k + /k + genotype is not observed with food efficiency. The results of Lowe and Merkley [10] showed that body weight gains/food consumption ratios tended to favour the K/k + genotype, which our results suggest at 10 weeks, although not significantly.…”
Section: Food Efficiencymentioning
confidence: 94%